PEMBERDAYAAN PEREMPUAN MELALUI PELATIHAN INOVASI PANGAN BERBASIS POTENSI LOKAL DI DESA KARANG SURAGA KABUPATEN SERANG - Nikki Prafitri; Tegar Attar Ardiansyah; Delis Raozatul Aulia (SEBA: Jurnal Pengabdian kepada Masyarakat, 2026)
Food security in Serang Regency needs to be supported by efforts to realize food diversification from the community's habit of consuming non-rice foods. Food diversification requires socialization and education efforts down to the village level. Karang Suraga Village, as one of the villages in Serang Regency, has potential local food sources such as cassava and fish, but innovation in these foods is still minimal. Demographically, the average woman in Karang Suraga Village is a housewife and actively participates in activities such as Posyandu (Integrated Health Post) and PKK (Family Welfare Movement). These two conditions present an opportunity to carry out community service focused on realizing food diversification from local foods based on women's empowerment. Women's empowerment is an effort to increase women's capacity and participation. The goal of this activity is to provide education and training for housewives to process local foods innovatively. The method used is to provide counseling on food diversification materials and practice processing local foods. The results of this activity indicate that the level of understanding of the activity targets regarding food diversification through innovation in local foods has increased 100% in all questionnaire statements during the post-test. The increased understanding of the activity's targets was facilitated by hands-on training on creating food innovations from cassava and fish into Sikalur nuggets. The results also demonstrated that training, involving women directly in creating local food innovations, can increase understanding and awareness of developing food diversification habits at the household level. Keywords: Women's empowerment; Food diversification; Local food innovation